2017
DOI: 10.15760/comminfolit.2017.11.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Library Impacts through First Year Course Assessment

Abstract: This study shows the value of library instruction in the building of first-year students' information literacy skills and it illustrates librarians as partners in leading student learning outcome assessment. Using research papers from a required first-year course, raters from units across the institution evaluated student information literacy (IL) skill development. Students performed at a "Proficient First Year" level for most information literacy skill areas. The authors found there was a significant correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Chan attributes this jump to library instruction. Favourable results after library instruction can also be seen with bibliographic analysis of first-year students' research papers (Luetkenhaus, Hvizdak, Johnson, & Schiller, 2017). Scored on six learning outcomes, first-year students performed at the 'Emerging' or 'Proficient First Year' level on five of the learning outcomes created by the research team.…”
Section: Theme 3: Assessment Studies Yield Conflicted Findings On Firmentioning
confidence: 93%
“…Chan attributes this jump to library instruction. Favourable results after library instruction can also be seen with bibliographic analysis of first-year students' research papers (Luetkenhaus, Hvizdak, Johnson, & Schiller, 2017). Scored on six learning outcomes, first-year students performed at the 'Emerging' or 'Proficient First Year' level on five of the learning outcomes created by the research team.…”
Section: Theme 3: Assessment Studies Yield Conflicted Findings On Firmentioning
confidence: 93%
“…Evaluation of student assignments completed in relation to library instruction sessions has been used as a technique for assessing student learning. Examples of student assignments include student research papers (Cooke & Rosenthal, ; Gamtso & Paterson, ; Luetkenhaus, Hvizdak, & Johnson, ), student worksheets administered as part of the instruction session (Matlin & Lantzy, ), and quizzes (Lowe, Boothe, & Tagg, ). Evaluation of student research papers is the most common way that this assessment technique has been implemented.…”
Section: Research Methods Used In Previous Workmentioning
confidence: 99%
“…Analysis of these final papers revealed students' ability to apply critical thought and provide well‐crafted recommendations, indicating that this collaborative, active‐learning exercise helped students move beyond merely learning information retrieval skills to learning how to analyze and apply information. Similarly, Luetkenhaus et al () used students' final research papers to measure the impact of library instruction for first‐year students, having raters from across the library provide feedback on students' demonstration of information literacy skills. Cooke and Rosenthal (), on the other hand, took a slightly different approach to analyzing student research papers, examining the citation pages of the papers as opposed to the content.…”
Section: Research Methods Used In Previous Workmentioning
confidence: 99%
“…Jiao, Onwuegbuzie, and Lichtenstein (1996) and Mech and Brooks (1997) demonstrated that firstyear students exhibited the highest rates of library anxiety, and students new to higher education naturally lack some of the skills and knowledge necessary to utilize academic libraries. Library instruction has been shown to increase first-year students' information literacy skills, whether the instruction takes the form of a one-shot session (Gilbert, 2009;Luetkenhaus, Hvizdak, Johnson & Schiller, 2017), a for-credit course (Cook, 2014), or general interactions with librarians (Lowe, Booth, Stone & Tagge, 2015). Van Scoyoc (2003) found that instruction reduced first-year students' library anxiety rates, but that study is over fifteen years old (as are other important library anxiety studies), and first-year students have changed significantly as today's students have come of age regularly using new and powerful information tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessment of library instruction is particularly important for institutions that devote considerable resources to library instruction for first-year students, such as the university under consideration in this study. Assessment of information literacy skills is common and is often used to justify large first-year instruction initiatives, but assessment of first-year students' emotional responses to the library is equally important, yet often neglected (Cook, 2014;Gilbert, 2009;Lowe, Booth, Stone & Tagge, 2015;Luetkenhaus, Hvizdak, Johnson & Schiller, 2017;Shao & Purpur, 2016). Ideally, library instruction for first-year students provides not only a base of information literacy skills to build on, but also an understanding of the library as a resource that they can return to for help throughout their academic careers.…”
Section: Introductionmentioning
confidence: 99%